DAYA TERIMA COOKIES SUBSTITUSI TEPUNG UBI JALAR KUNING DAN TEPUNG IKAN BILIS SEBAGAI ALTERNATIF PMT IBU HAMIL - Alfiyatur Rahmawati; Mulyanita; Martinus Ginting (Jurusan Gizi Poltekkes Pontianak, 2025)
Pregnant women with Chronic Energy Deficiency (CED) are at high risk of delivering babies with low birth weight. One alternative to address this issue is to develop cookies made from yellow sweet potato and anchovy flour, which are high in energy and protein content to support the nutrition of pregnant women. This study aims to evaluate the acceptability of cookies with substituted yellow sweet potato flour and anchovy flour in concentrations of (40:10), (35:15), and (30:20). The method used is experimental. The results of the Friedman statistical test showed that the variations in yellow sweet potato flour and anchovy flour formulations did not affect cookie acceptability. Based on organoleptic tests, including color, aroma, texture, and taste, the cookies in treatment P1 (10% anchovy flour) were the most preferred. The conclusion of this study indicates that cookies with the addition of 10% anchovy flour (P1) have a light brown color, a distinctive buttery aroma, a crispy texture, and a balanced sweet taste, making them the panelists' favorite. Statistical test results also showed that variations in yellow sweet potato flour and anchovy flour did not have a significant effect on the cookies' characteristics.